Inovasi Pembelajaran SMK Sultan Hasanuddin Gowal: Pelatihan Media Pembelajaran Berbasis Quizziz AI - Hanapi, Khaerunnisa; Marsha, Marsha (Jurnal Pengabdian kepada Masyarakat UBJ, 2025)
Innovation in learning media continues to evolve with the rapid advancement of technology. One platform that is widely used in education today is Quizziz, which offers AI-based features to enhance the quality and effectiveness of learning and evaluation. This activity involves teachers at SMK Sultan Hasanuddin Gowa in utilizing Quizziz technology, equipped with artificial intelligence features, to create interactive learning media and effective evaluations. Through this community service program, teachers are expected to improve their skills in designing engaging teaching materials, speeding up the evaluation process, and providing more personalized feedback to students. The outcomes of this initiative show an increase in teachers' understanding and motivation in using the latest educational technology, which is expected to enhance the overall quality of the teaching and learning process at SMK Sultan Hasanuddin Gowa.